Isolation and identification of causal agents associated with duck mortality in Haor areas of Bangladesh - Sourav Chakraborty; Sakib Anzum Pranto; Md Muket Mahmud; Sharmin Sultana Misty; Md Mamun Or Rashid; Md Hadiuzzaman; Mohammad Asir Uddin; Mohammad Ferdousur Rahman Khan; Md Tanvir Rahman; Md Alimul Islam; Muhammad Tofazzal Hossain (Research in Agriculture Livestock and Fisheries, 2025)
The duck population is concentrated mostly in the north and northeast wetland areas in Bangladesh. They are reared in close contact with domestic fowls and can be a potential source of many bacterial and viral diseases, as sudden death of ducks is frequently evident. This study aimed to identify the causal agents behind the mortality of ducks in the haor areas of Bangladesh. In total, 66 dead ducks were collected from several locations of different haors in Mymensingh, Kishoreganj, and Netrokona districts. Internal organs of ducklings (n=21) and adult ducks (n=45) were collected as samples. Part of each sample was enriched in nutrient broth for the growth of bacteria, followed by culture in specific media, staining, and biochemical tests were conducted for the primary confirmation of the bacterial isolates. Additionally, inoculum was prepared to propagate viruses in duck embryos. Specific primers were used for the detection of bacterial and viral isolates by PCR. Overall, Escherichia coli (75.75%), Salmonella spp. (12.12%), Staphylococcus spp. (7.57%), Pasteurella spp. (12.12%) and duck plague virus (13.64%) were detected by PCR. All the bacterial and viral isolates were found to be the cause of different duck diseases and major agents for duck mortality in the haor areas. However, they can also be a potential source of pathogen transmission to other domestic fowls. Res. Agric. Livest. Fish. Vol. 11, No. 3, December 2024: 343-352